2019
DOI: 10.1111/all.13684
|View full text |Cite
|
Sign up to set email alerts
|

Der p 1‐specific regulatory T‐cell response during house dust mite allergen immunotherapy

Abstract: Background: Allergen-specific immunotherapy (AIT) is the only available treatment for allergic diseases that can induce specific immune tolerance to allergens. The key mechanisms involved in this process include changes in allergen-specific regulatory T (Treg) cells. Methods:We studied 25 allergic rhinitis patients undergoing subcutaneous house dust mite-specific immunotherapy. Peripheral blood mononuclear cells were studied before and after 10, 30 weeks, and 3 years of AIT. Der p 1-specific T regulatory cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
70
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 56 publications
(59 reference statements)
6
70
1
3
Order By: Relevance
“…4 Whereas AIT is an effective treatment in the patients with house dust mites (HDM) allergy, the role of HDM allergen-specific IgD remains to be fully evaluated. 4,7 The major HDM allergens are represented by Der p/f 1, Der p/f 2, and Der p/f 23. 8 In this report, we have shown that Der p 2-specific IgD-producing B cells increased during the course of AIT that might be correlated to the successful development of HDM tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Whereas AIT is an effective treatment in the patients with house dust mites (HDM) allergy, the role of HDM allergen-specific IgD remains to be fully evaluated. 4,7 The major HDM allergens are represented by Der p/f 1, Der p/f 2, and Der p/f 23. 8 In this report, we have shown that Der p 2-specific IgD-producing B cells increased during the course of AIT that might be correlated to the successful development of HDM tolerance.…”
mentioning
confidence: 99%
“…From a cohort study of 75 HDM allergic patients undergoing SCIT with HDM allergen extracts, we selected 6 treated asthmatic patients to investigate Der p 2-specific B cells. 4,7 The patient characteristics are shown in the Table S1. Peripheral blood mononuclear F I G U R E 2 Improved asthma control correlated with plasma Der p 2-specific IgD levels.…”
mentioning
confidence: 99%
“…113 Furthermore, allergen-specific Tregs have been shown to expand following AIT for HDM and grass pollen allergies thereby increasing the ratio of allergen-specific Tregs over effector T cells. 32,33,114,115 To facilitate translation towards routine measurements of T-cell biomarkers, immunophenotyping approaches have been developed that only use membrane markers and allow for direct ex vivo T-cell evaluation without in vitro cell culture. The CD4+CD25+CD127phenotype specifically distinguishes human Treg, 116,117 and these cells can be quantified in allergic patients 31 with increases following SLIT for grass pollen 11 and AIT in HDM-allergic individuals.…”
Section: T Cellsmentioning
confidence: 99%
“…The CD4+CD25+CD127phenotype specifically distinguishes human Treg, 116,117 and these cells can be quantified in allergic patients 31 with increases following SLIT for grass pollen 11 and AIT in HDM-allergic individuals. 32 Furthermore, chemokine receptor expression patterns correlate strongly with Th cell function [118][119][120] and can be used to identify Th1 (CCR6-CXCR3+CCR4-), Th2 (CCR6-CXCR3-CCR4+) and Th17…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation